2020
DOI: 10.1017/wet.2020.2
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide programs for control of glyphosate-resistant canola (Brassica napus) in glyphosate-resistant soybean

Abstract: Glyphosate-resistant (GR) canola is a widely grown crop across western Canada and has quickly become a prolific volunteer weed. Glyphosate-resistant soybean is rapidly gaining acreage in western Canada. Thus, there is a need to evaluate herbicide options to manage volunteer GR canola in GR soybean crops. We conducted an experiment to evaluate the efficacy of various PRE and POST herbicides applied sequentially to volunteer GR canola and to evaluate soybean injury caused by these herbicides. Trials were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Similarly, Mierau et al. (2020) found a 60% reduction in soybean yield with an infestation of volunteer canola at a density of 60 plants m −2 .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Similarly, Mierau et al. (2020) found a 60% reduction in soybean yield with an infestation of volunteer canola at a density of 60 plants m −2 .…”
Section: Introductionmentioning
confidence: 82%
“…In a study conducted at Glyndon, Minnesota, Stachler and Luecke (2009) found that volunteer canola at 180 plants m −2 resulted in a nearly complete loss of sugar beet crop yield. Similarly, Mierau et al (2020) found a 60% reduction in soybean yield with an infestation of volunteer canola at a density of 60 plants m −2 .…”
Section: Introductionmentioning
confidence: 86%
“…However, limitation of volunteer canola seed production in crops grown subsequent to canola is imperative to limiting persistence of this weed (Geddes and Gulden, 2018;Geddes and Gulden, 2021). Soybean and canola have similar herbicide resistance traits (Mierau et al, 2020). In western Canada, volunteer canola is the most abundant weed species present after post-emergence weed control in soybean (Leeson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to multiple herbicide sites-of-action exacerbates the impact of kochia, wild oat, and volunteer canola on Canadian farms by limiting the herbicide options available for their management [ 5 , 6 , 7 ]. In the Canadian prairies, resistance to 3, 4, and 3 herbicide sites-of-action have been documented in kochia, wild oat, and volunteer canola, respectively [ 8 ].…”
Section: Introductionmentioning
confidence: 99%